On sea-ice advance and retreat in the Indian Ocean sector and off Lutzow-Holmbukta, Antarctica - Shuki Ushio (Antarctic Record, 2006)
Characteristics of sea ice variations in the Indian Ocean sector and off Lutzow-Holmbukta, Antarctica, have been described with satellite data archived since the 1970s. In the Indian Ocean sector, the period of maximum ice extent is generally reached in October, a month later than in other sectors. The probable reason for the delay is eastward sea-ice drift from the Weddell Sea sector west of the Indian Ocean sector. During the ice melt season, the highest rate of ice retreat from November to December appears in the Indian Ocean sector. Also, the ice edge along 40 degrees east longitude off Lutzow-Holmbukta shows a remarkable delay pattern at the beginning of autumn ice extent season and rapid retreat of the ice edge in the spring melt season. These features are qualitatively explainable due to Cosmonaut Polynya formation.